Diet quality over time is associated with better development in rural Nepali children. Issue 3 (11th February 2020) - Miller, Laurie C.; Neupane, Sumanta; Joshi, Neena; Shrestha, Merina; Neupane, Shailes; Lohani, Mahendra; Thorne‐Lyman, Andrew L.
Abstract: Developmental delays affect between 150 and 200 million children <5 years of age worldwide. Outside of diet supplement studies, relatively little is known about the relationships between diet quality and developmental status in resource‐poor settings. We examined associations between different aspects of dietary quality (dietary diversity score [DDS] and animal‐source food [ASF] consumption) and child development (assessed using the Ages and Stages Questionnaire‐3 [ASQ‐3]) among children whose families were enrolled in a community development intervention trial (implemented by Heifer Nepal) in western Nepal. Two sets of analyses were performed: (a) cross‐sectional Sample ( N = 629) seen at the endline survey and (b) longitudinal sample ( N = 269) with complete dietary records (six surveys over 48 months). In both samples, child development was significantly related to household wealth, maternal education, and especially home environmental quality. In the cross‐sectional sample, greater consumption of eggs (adjusted odds ratio [aOR] 0.80, p = .04) or dairy products (aOR 0.95, p = .05) over the previous 7 days significantly reduced odds of low total ASQ score, by logistic regression analysis. In the longitudinal sample, only egg consumption and cumulative DDS and ASF scores were associated with significantly reduced odds of low total ASQ score (aORs 0.59–0.89). In adjusted linear regression analysis, both cumulative DDS (β [CI]: 1.92 [0.4, 3.5]) and ASF scores (2.46 [0.3, 4.7]) were significantly associated with greater continuous total child development. Programmes targeting child development must address home environmental quality as well as long‐term diet quality.